If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6h + 1 = 2h + -3 Reorder the terms: 1 + 6h = 2h + -3 Reorder the terms: 1 + 6h = -3 + 2h Solving 1 + 6h = -3 + 2h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-2h' to each side of the equation. 1 + 6h + -2h = -3 + 2h + -2h Combine like terms: 6h + -2h = 4h 1 + 4h = -3 + 2h + -2h Combine like terms: 2h + -2h = 0 1 + 4h = -3 + 0 1 + 4h = -3 Add '-1' to each side of the equation. 1 + -1 + 4h = -3 + -1 Combine like terms: 1 + -1 = 0 0 + 4h = -3 + -1 4h = -3 + -1 Combine like terms: -3 + -1 = -4 4h = -4 Divide each side by '4'. h = -1 Simplifying h = -1
| -(-6x-3y-29)= | | 7p-5=h+6 | | 6+0.1x=0.15x+I | | 26x-2-7x=7x-7-7x | | 7n+12=-36 | | X+4=-2x | | x+10x+25(40)-25(2x)=376 | | 2+4(6n-2)=-150 | | -3(-2x-9)=15 | | -4a-2a=-12 | | 19w=-6w+41 | | 3p-19=7p+4p-43 | | 4x-20+y=180 | | -w-2(w+3)=5w-3-w | | 60=-12z | | 15+5x=-5 | | 3z-3=z+2 | | 3x-4=4x+18+2(x+3) | | 12x+32=12x-6 | | 9=8n+17 | | 6(-2-4x)=156 | | (-1)(7)= | | 3x^2+7-2=0 | | 1-4x-3x=-6 | | 36=4*4 | | 36=4*7 | | 3cos(x)+4sin(x)=2 | | 14+8z=-14+8z | | 20r^2+7=45r+7 | | 4(5+2b)=12 | | 36=4*6 | | 1+3n=16 |